FORECASTING ANALYSIS OF PHARMACEUTICALS AND MEDICAL DEVICES IN A CATEGORY NEEDED IN 2011 - Devie Ronald Lumy (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Forecasting of pharmaceuticals and medical devices are an effort to estimate the needs of pharmaceuticals and medical devices in hospital. Pharmaceuticals and medical devices of class A based on ABC analysis represents a small amount in stock but has the largest inventory value. This study aimed to determine the exact forecasting that used to estimate the needs of pharmaceuticals and medical devices in class A in the Pharmacy Department Immanuel Hospital Bandung. This research was a descriptive study with retrospective data collection. Forecasting analysis of pharmaceuticals and medical devices needed used the average of last period, seasonal variation, and seasonal index with trend adjustment in 2011. Forecasting analysis was calculated based on consumtion of pharmaceuticals and medical devices in 2008-2010. Accuracy of forecasting methods were determined by the smallest value of mean absolute deviation (MAD) and mean squared error (MSE).  The results from 24 samples of pharmaceuticals and medical devices in class A showed that there were 12 samples (50%) with the smallest MAD for seasonal index with trend adjustment method, 8 samples (66.67%) with the smallest MAD values for average of last period method, and 4 samples (16.67%) with the smallest MAD for seasonal variation method. According to MSE, there were 14 samples (58.33%) with the smallest MSE value for the seasonal index with trend adjustment method, 8 samples (66.67%) with the smallest MSE value for the average of last period method, and 2 samples (8, 33%) with the smallest MSE for seasonal variation method. It can be concluded that seasonal index with trend adjustment analysis was better compared the method of seasonal variation and the average of last period to forecasting needs of pharmaceuticals and medical devices in A category.Keywords:seasonal index with trend adjustment, ABC Analysis, Immanuel Hospital Bandung